Asuhan Keperawatan Keluarga Pada Keluarga Dengan Diabetes Mellitus Di Wilayah Kerja Puskesmas Lubuk Alung Kabupaten Padang Pariaman - Nadila Ramadhani; Armaita .; Sandra Dewi; Hasmita . (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Diabetes Mellitus is a non-communicable disease with a continuously increasing incidence and is a public health problem (WHO 2021). Data in Padang Pariaman Regency shows an increase in cases from 5,238 in 2024 to 8,932 in 2025. The purpose of this paper is to describe family nursing care for families with Diabetes Mellitus in the Lubuk Alung Community Health Center (Puskesmas) working area. Diabetes Mellitus can cause complaints such as increased thirst, frequent hunger, fatigue, and tingling, and carries a risk of complications. The method used is a case study with a nursing process approach including assessment, diagnosis, intervention, implementation, and evaluation. Case analysis revealed the main problems were acute pain, unstable blood glucose levels, and ineffective health maintenance. Interventions focused on health education, monitoring the patient's condition, and increasing the family's role in care. The results indicate an increase in family knowledge and independence in caring for patients and efforts to prevent complications.  The recommendations given are that families are expected to be able to support patients in controlling blood sugar regularly every month and taking medication regularly, and health workers can improve education and family nursing services to support optimal management of Diabetes Mellitus.